2020
DOI: 10.1007/s11136-020-02633-z
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of cancer patients at palliative care units in developing countries: systematic review of the published literature

Abstract: Purpose This systematic review aims to summarize factors that influence the quality of life (QOL) of advanced cancer patients in palliative care (PC) in developing countries. Understanding this context in developing countries milieu is necessary; however, this outcome is rarely reported. Methods Following the PRISMA guidelines, the electronic databases MEDLINE, Embase, CINAHL, and Web of Science were systematically searched using the search te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
1
5

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 72 publications
1
25
1
5
Order By: Relevance
“…It may be that cancer patients with varying degrees of anorexia, pain and other symptoms, and coupled with nancial pressure that lead they are easy to anxiety and depression, the mood is di cult to calm and ease. Related studies have shown that spiritual care affects the clinical outcomes, relieves pain and contributes to health promotion, so that patients can feel content and enjoy peace in mind [42][43]. Therefore, under the condition of solving the economic pressure and using treatment methods to alleviate discomfort symptoms, it is necessary to meet their spiritual needs as the premise and provide appropriate measures of spiritual care.…”
Section: Discussionmentioning
confidence: 99%
“…It may be that cancer patients with varying degrees of anorexia, pain and other symptoms, and coupled with nancial pressure that lead they are easy to anxiety and depression, the mood is di cult to calm and ease. Related studies have shown that spiritual care affects the clinical outcomes, relieves pain and contributes to health promotion, so that patients can feel content and enjoy peace in mind [42][43]. Therefore, under the condition of solving the economic pressure and using treatment methods to alleviate discomfort symptoms, it is necessary to meet their spiritual needs as the premise and provide appropriate measures of spiritual care.…”
Section: Discussionmentioning
confidence: 99%
“…Due to an increase in the effectiveness of anti-cancer treatment [44] and an increase in life expectancy in cancer patients [45], the long-term complications will probably be observed more often, resulting in increasing role of the quality of life [46]. Taking this into account, it must be emphasized that the systematic review by Lis et al [47], assessing the role of nutritional status in predicting quality of life in cancer individuals, indicated that correcting malnutrition may improve quality of life in cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…27 Also, spirituality and religiosity are key components of Indonesian culture and influence the motivation to care for cancer patients. 27 For instance, studies reported that spiritual and religious practices in Indonesia and most developing countries acted as a positive factor for providing comfort and support for a sick family member 26 , 28 and positively affected cancer patients’ ability to cope. 29 Since most of our patients were religious individuals (around 90%), this aspect adds to the explanation of our findings.…”
Section: Discussionmentioning
confidence: 99%